The Study of Religion in Sweden: Past, Present and Future - Bogdan, Henrik (Bloomsbury Publishing Plc, 2024)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Contributors -- Introducing the Study of Religion in Sweden -- Part I Historical Approaches -- Chapter 1 Ancient Near Eastern Religions (Therese Rodin and Heike Peter) -- Chapter 2 Old Norse Religion (Olof Sundqvist) -- Chapter 3 Indigenous Religions (Daniel Andersson and Bodil Liljefors Persson) -- Chapter 4 Judaism (Svante Lundgren and Martin Lund) -- Chapter 5 Islam (Göran Larsson, Susanne Olsson and Simon Sorgenfrei) -- Chapter 6 Indian Religions (Kristina Myrvold, Katarina Plank and Ferdinando Sardella) -- Chapter 7 Western Esotericism (Henrik Bogdan) -- Chapter 8 New Religious Movements and New Age Spirituality (Peter Åkerbäck and Sanja Nilsson) -- Part II Social Scientific Approaches -- Chapter 9 Psychology of Religion (Göran Ståhle and Tomas Lindgren) -- Chapter 10 Sociology of Religion (Mia Lövheim and Magdalena Nordin) -- Chapter 11 The Cognitive Science of Religion (Jonas Svensson and Egil Asprem) -- Chapter 12 Religious Education (Christina Osbeck and Olof Franck) -- Part III Themes in the Study of Religion in Sweden -- Chapter 13 Comparative Studies (Stefan Arvidsson and Peter Jackson Rova) -- Chapter 14 Ritual Studies (Anne-Christine Hornborg) -- Chapter 15 Lived Religion (Daniel Enstedt, Jessica Moberg and Katarina Plank) -- Chapter 16 Gender Studies (Manon Hedenborg White) -- Chapter 17 Violence (Tomas Lindgren, Göran Larsson and Isak Svensson) -- Afterword: (Jenny Berglund and Tim Jensen) -- Index of names.